Bridging AI and Statistics: Comparative Evaluation of SPSS and ChatGPT in Educational Data Processing - Rahmatta Thoriq Lintangesukmanjaya; Binar Kurnia Prahani; Dwikoranto Dwikoranto (Journal of Innovative Technology and Sustainability Education, 2025)
Objective: This study aims to compare the results of statistical data analysis using SPSS and Artificial Intelligence (AI), specifically ChatGPT, in processing students’ learning outcomes. A quantitative experimental method was employed with a sample of 100 numerical data points representing students’ academic performance. Method: This research is a comparative study, with processing outcomes in SPSS and ChatGPT.  Results:  Both SPSS and ChatGPT were utilized to perform statistical tests and analyze the same dataset. The findings indicate that both tools produced consistent results, demonstrating ChatGPT’s potential as a complementary analytical tool. However, SPSS remains superior in terms of accuracy, academic legitimacy, and the availability of comprehensive features officially recognized in the research community. ChatGPT offers advantages in its simplicity, accessibility, and efficiency, particularly for quick analysis without software installation, making it a practical tool for educators and novice researchers. Novelty: In formal academic research contexts, SPSS remains the primary choice for ensuring methodological rigor and credibility, while AI-driven tools such as ChatGPT can serve as effective companions to support the analytical process and facilitate statistical learning. This study highlights the potential synergy between traditional statistical software and emerging AI technologies, emphasizing the importance of selecting tools that align with research needs, context, and academic standards. The findings provide insights into the evolving role of AI in research practices, suggesting that while AI enhances accessibility and user experience, conventional statistical software remains indispensable for high-stakes research validation.